Oestrous and conception rate in Saanen goats synchronized with medroxyprogesterone acetate (MAP) at two times of the year - Garcia A., Kenyi (2020)
The study aimed to evaluate the rates of visual oestrous and conception in Saanen goats subjected to oestrus synchronization at two seasons of the year. Hormonal synchronization was done using an intravaginal sponge impregnated with medroxyprogesterone acetate (MAP), for 11 days. In addition, 48 hours before sponge removal, 300 IU equine chorionic gonadotropin (eCG) and 125 µg cloprostenol were administered. The goats that showed heat were mounted by fertile males. The pregnancy diagnosis was done 60 days after the service by transrectal ultrasound. The rate of presentation of heat was 86.7 and 96.7% for the anoestrous season (January-February) and the cyclicity season (March-April), respectively, without significant difference between periods. The conception rate was 88.5 and 62.1% for the periods January-February and March-April, respectively (p<0.05). It is concluded that the use of MAP impregnated intravaginal sponges for the synchronization of oestrus in Saanen goats is effective, regardless of the time of year.